Papers of Ninette Dutton - Dutton, Ninette, 1923-2007. (1890)
A large component of MS 10111 comprises correspondence. There are letters from many well known people in the literary and arts world, some spanning a number years, and family letters which document many stages of Ninette Dutton's life. Principal correspondents include Richard Adlington, Sir Walter Campbell, Bruce Chatwin, Dymphna and Manning Clark, Walter Crocker, Denison Deasey, Russell Drysdale, Sumner Locke-Elliott, Shirley Hazzard, Max Harris, Peg Hesse (Princess Margaret of Hesse), Barry Humphries, Alister Kershaw, David Marr, Mirka Mora, Les Murray, Gino Nibbi, Elizabeth Riddell, Nicholas Shakespeare, Jeffrey Smart, Tom Shapcott, Randolph Stow and Patrick White. Also included in the collection are drafts and original illustrations for Dutton's published works, photographs, newspaper cuttings, travel journals and early family papers (50 boxes, 4 fol. boxes, 1 elephant folio).
Manuscript reference no.: MS 10111.
National Library of Australia Oral History collection ORAL TRC 1/1113.
Author, enamellist, gardener and botanical artist. Together with her husband, Geoffrey, Ninette Dutton was an important part of the Australian literary scene, establishing friendships with many well known authors through their involvment with both local and international literary events. Ninette Dutton published a number of books relating to her love of the Australian landscape and gardening, often illustrated with her own botanical drawings. As well she published several autobiographical works and contributed a weekly column, "The passionate gardener" to The Advertiser, Adelaide from 1989-1991. Ninette Dutton established a reputation as an enamellist, studying the art overseas in Europe and the United States. She held exhibitions of her work, received commissions for works in public spaces and is represented in collections both in Australia and overseas.
Finding aid available online.
Keywords: Dutton, Ninette, -- 1923-2007 -- Archives; Artists -- Australia -- Archives; Women artists -- Australia -- Archives; Authors, Australian -- 20th century -- Archives; Art, Australian -- 20th century; Enamel and enameling; Gardens -- Australia; Garden writing; Artists; Authors